Insights into the nuclear-organelle DNA integration in Cicuta virosa (Apiaceae) provided by complete plastid and mitochondrial genomes - Seongjun Park; Yong Hwang; Heesoo Kim; KyoungSu Choi (BMC Genomics)
Abstract Background Gene transfer between the organelles and the nucleus plays a central role in shaping plant genome evolution. The identification and analysis of nuclear DNA of plastid (NUPTs) and mitochondrial (NUMTs) origins are important for exploring the extent of intracellular DNA transfer in genomes. Results We report the complete plastid and mitochondrial genomes (plastome and mitogenome) of Cicuta virosa (Apiaceae) as well as a draft nuclear genome using high-fidelity (HiFi) PacBio sequencing technologies. The C. virosa plastome (154,449 bp) is highly conserved, with a quadripartite structure, whereas the mitogenome (406,112 bp) exhibits two chromosomes (352,718 bp and 53,394 bp). The mitochondrial-encoded genes (rpl2, rps14, rps19, and sdh3) were successfully transferred to the nuclear genome. Our findings revealed extensive DNA transfer from organelles to the nucleus, with 6,686 NUPTs and 6,237 NUMTs detected, covering nearly the entire plastome (99.93%) and a substantial portion of the mitogenome (77.04%). These transfers exhibit a range of sequence identities (80–100%), suggesting multiple transfer events over evolutionary timescales. Recent DNA transfer between organelles and the nucleus is more frequent in mitochondria than that in plastids. Conclusions This study contributes to the understanding of ongoing genome evolution in C. virosa and underscores the significance of the organelle-nuclear genome interplay in plant species. Our findings provide valuable insights into the evolutionary processes that shape organelle genomes in Apiaceae, with implications for broader plant genome evolution.